2016
DOI: 10.18632/oncotarget.10639
|View full text |Cite
|
Sign up to set email alerts
|

A cancer specific hypermethylation signature of the TERT promoter predicts biochemical relapse in prostate cancer: a retrospective cohort study

Abstract: The identification of new biomarkers to differentiate between indolent and aggressive prostate tumors is an important unmet need. We examined the role of THOR (TERT Hypermethylated Oncological Region) as a diagnostic and prognostic biomarker in prostate cancer (PCa).We analyzed THOR in common cancers using genome-wide methylation arrays. Methylation status of the whole TERT gene in benign and malignant prostate samples was determined by MeDIP-Seq. The prognostic role of THOR in PCa was assessed by pyrosequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 52 publications
11
60
0
Order By: Relevance
“…Association between higher methylation at cg11625005 and poorer patient survival has been previously reported (Castelo-Branco et al, 2013, 2016; Gojo et al, 2017; Seynnaeve et al, 2017); our results extend these findings to two additional cancer types, suggesting that hypermethylation of the TERT promoter may represent a broadly applicable prognostic marker. To our knowledge, our data showing a more positive outcome for stomach adenocarcinoma patients with higher methylation at cg11625005 or with high EZH2 expression and suggest that the mechanisms driving survival in these patients may be distinct.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Association between higher methylation at cg11625005 and poorer patient survival has been previously reported (Castelo-Branco et al, 2013, 2016; Gojo et al, 2017; Seynnaeve et al, 2017); our results extend these findings to two additional cancer types, suggesting that hypermethylation of the TERT promoter may represent a broadly applicable prognostic marker. To our knowledge, our data showing a more positive outcome for stomach adenocarcinoma patients with higher methylation at cg11625005 or with high EZH2 expression and suggest that the mechanisms driving survival in these patients may be distinct.…”
Section: Discussionsupporting
confidence: 89%
“…Methylation levels at cg11625005 are negatively correlated with patient survival in some cancers (Castelo-Branco et al, 2013, 2016; Gojo et al, 2017). We therefore analyzed overall survival (OS) with respect to methylation and TERT promoter mutation in patient samples for a range of cancers within the TCGA.…”
Section: Resultsmentioning
confidence: 99%
“…In UBC, TERT p Mut is an early event while THOR hypermethylation is associated with disease progression and increased TERT expression. This pattern has been observed in other cancer types …”
Section: Discussionsupporting
confidence: 84%
“…Our group and others have identified a parallel epigenetic control of telomerase activation in cancer. Specifically, a region located upstream of the core mutation area, within the TERT promoter, termed THOR ( TERT Hypermethylated Oncological Region) is hypermethylated in many TERT‐expressing cancers, is associated with telomerase activation and predicts clinical outcomes in multiple tumor types . We therefore hypothesized that dual mechanisms activate telomerase in UBC.…”
Section: Introductionmentioning
confidence: 99%
“…showed that coexistence of TERT promoter and BRAF or NRAS mutations was associated with a 2-fold reduced rate of disease-free survival and a 5-fold reduced rate of melanoma-specific survival in patients with stage I and II melanoma26. TERT promoter hypermethylation is also an effective molecular marker for prognosis in a number of cancer types, and was previously shown to correlate with increased TERT expression in a subset of melanomas2933373839.…”
Section: Discussionmentioning
confidence: 98%